Women reporting sport: Still a man's game?. (May 2016) - Franks, Suzanne; O'Neill, Deirdre
While it is generally known that sports journalism is an area of gender disparity, no major academic study has established the proportion of women sports writers in the UK press. Although female sports broadcasters have increased their visibility in the United Kingdom, the same is not true in the print media. This research first examines the current visibility of women sports journalists in the national UK press, by counting by-lines according to gender. Second, a study explores if the 2012 London Olympic Games had any effect on the proportion of female sports writers in the UK press, by comparing sports by-lines in a sample 6 months before and after the games. Furthermore, these results are compared to a decade earlier to see if the situation has improved. The findings indicate that the proportion of female sports writers in the UK press is lower than in comparable countries, with little improvement over time.